Operasi Taufan Al-Aqsa 2023: Analisis Dinamika Strategi Perang Hamas terhadap Israel - Candelaria, Arizki Putri (Journal of Integrative International Relations, 2025)
The Al-Aqsa Flood Operation launched by Hamas on October 7, 2023, marked a significant shift in Hamas’s warfare strategy against Israel. This study analyzes the dynamics of Hamas’s war strategy during the operation using the concepts of asymmetric warfare and guerrilla strategy. The research adopts a qualitative-descriptive approach, employing documentation techniques from various primary and secondary sources. The findings indicate that Hamas developed a more coordinated guerrilla tactic, including the use of tunnels, deception, ambushes, sabotage, as well as new tactics such as saturation attacks, drone strikes, and propaganda. This operation had not only military impacts on Israel but also broad political and social consequences. Hamas succeeded in exploiting weaknesses in Israeli intelligence and leveraged geopolitical momentum to strengthen its position in the prolonged conflict with Israel. Operasi Taufan Al-Aqsa yang dilancarkan oleh Hamas pada 7 Oktober 2023 menandai perubahan signifikan dalam strategi perang Hamas terhadap Israel. Penelitian ini menganalisis dinamika strategi perang Hamas dalam operasi tersebut dengan menggunakan konsep perang asimetris dan strategi gerilya. Pendekatan penelitian yang digunakan adalah kualitatif-deskriptif dengan teknik dokumentasi dari berbagai sumber primer dan sekunder. Hasil penelitian menunjukkan bahwa Hamas mengembangkan taktik gerilya yang lebih terkoordinasi, termasuk penggunaan terowongan, deception, ambush, sabotase, serta taktik baru seperti saturation attack, drone attack, dan propaganda. Operasi ini tidak hanya berdampak pada Israel secara militer tetapi juga memiliki konsekuensi politik dan sosial yang luas. Hamas mampu mengeksploitasi kelemahan intelijen Israel dan memanfaatkan momen geopolitik untuk memperkuat posisinya dalam konflik berkepanjangan dengan Israel.